Temporal relationship between sleep duration and obesity among Chinese Han people and ethnic minorities - Zhengxing Xu; Min Chen; Yuntong Yao; Lisha Yu; Peijing Yan; Huijie Cui; Ping Li; Jiaqiang Liao; Ben Zhang; Yuqin Yao; Zhenmi Liu; Xia Jiang; et al. (BMC, 2023)
Abstract Background No studies have assessed the association between sleep duration and obesity in Chinese ethnic minorities. Whether the relationship between sleep duration and obesity is different between Chinese Han people and Chinese ethnic minorities remains unclear. The study aimed to explore the relationship between sleep duration and obesity among Chinese Han people and Chinese ethnic minorities. Methods We applied data from the Guizhou Population Health Cohort Study (GPHCS), which 9,280 participants were recruited in the baseline survey from 2010 to 2012, and 8,163 completed the follow-up survey from 2016 to 2020. A total of 5,096 participants (3,188 Han Chinese and 1,908 ethnic minorities) were included in the ultimate analysis. Information on sleep duration (total 24-hour sleep time), body mass index (BMI), and waist circumference (WC) was collected at the baseline and follow-up survey, respectively. Cross-lagged panel analyses were conducted to explore the temporal relationship between sleep duration and obesity for Han people and ethnic minorities. Results For Han people, the results from cross-lagged panel analyses indicated that baseline sleep duration was significantly associated with follow-up BMI (βBMI = -0.041, 95% CIBMI: -0.072 ~ -0.009) and follow-up WC (βWC = -0.070, 95%CIWC: -0.103 ~ -0.038), but baseline BMI (βBMI = -0.016, 95% CIBMI: -0.050 ~ 0.018) and baseline WC (βWC = -0.019, 95% CIWC: -0.053 ~ 0.016) were not associated with follow-up sleep duration. In addition, the relationship between baseline sleep duration and follow-up BMI was gender-specific and significant only in the Han people female (βBMI = -0.047, 95% CIBMI: -0.090 ~ -0.003) but not in the Han people male (βBMI = -0.029, 95% CIBMI: -0.075 ~ 0.016). For ethnic minorities, the results indicated that there was no relationship between sleep duration and obesity at all, either from sleep duration to obesity (βBMI = 0.028, 95%CIBMI: -0.012 ~ 0.068; βWC = 0.020, 95%CIWC: -0.022 ~ 0.062), or from obesity to sleep duration (βBMI = -0.022, 95%CIBMI: -0.067 ~ 0.022; βWC = -0.042, 95%CIWC: -0.087 ~ 0.003). Conclusion The relationship pattern between sleep duration and obesity across Han people and ethnic minorities is different. Future sleep-aimed overweight and obesity intervention should be conducted according to population characteristics.